SOME ASPECTS OF THE STUDENTS’ READINESS TO ACTIVITY IN AN ENVIRONMENT OF INSTITUTIONAL REPOSITORY - Oleksyuk О.Р. (Journal of Information Technologies in Education (ITE), 2014)
The article investigated the state of development of specific digital libraries – institutional repositories. In the article described the features of their use in scientific research work of the students. This research contains an interview. It identified the major trends of use e-information in the studying and scientific work.